2019
DOI: 10.1097/jxx.0000000000000160
|View full text |Cite
|
Sign up to set email alerts
|

Improving perceptions of patient safety through standardizing handoffs from the emergency department to the inpatient setting: a systematic review

Abstract: Background and purpose: Patient handoffs have long been identified as a potentially challenging time for patients because poor communication produces numerous complications. This is especially true with regards to patient care handoffs between areas such as the emergency department (ED) and inpatient setting. The purpose of this systematic review is to analyze existing literature pertaining to standardized handoffs between the ED and inpatient setting and its effect on perceived patient safety to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…118 Use of standardized forms used during a variety of transfers between levels of care has improved communication of patients' advanced directives, safety perceptions, patient satisfaction, and other outcomes. 9,10,19,[119][120][121] Standardized handoff tools together with coordinated medication reconciliation increase patient satisfaction regarding medication knowledge and meeting healthrelated goals, especially when speaking with a pharmacist about their medications. 25 Unlike studies assessing patient satisfaction with institutional services, the Task Force has identified no recent studies of prescriber satisfaction or engagement with pharmacy TOC services.…”
Section: Services Originating Within Hospitals and Other Institutional Settingsmentioning
confidence: 99%
“…118 Use of standardized forms used during a variety of transfers between levels of care has improved communication of patients' advanced directives, safety perceptions, patient satisfaction, and other outcomes. 9,10,19,[119][120][121] Standardized handoff tools together with coordinated medication reconciliation increase patient satisfaction regarding medication knowledge and meeting healthrelated goals, especially when speaking with a pharmacist about their medications. 25 Unlike studies assessing patient satisfaction with institutional services, the Task Force has identified no recent studies of prescriber satisfaction or engagement with pharmacy TOC services.…”
Section: Services Originating Within Hospitals and Other Institutional Settingsmentioning
confidence: 99%
“…Seven reviews examined interventions relating to patient handover processes and transitions in care. Patient handover processes and transitions in care interventions include handover tools [27][28][29][30], bedside registration [19,31], discharge planning [31], discharge communication [32], process protocols and guidelines [27,29,30], handover training [29], dedicated offload nurse for triaging and assessing EMS patients [30], nurse discharge coordinators [33]. A description of the characteristics for each Graphical presentation for ROBIS results across all included reviews.…”
Section: Care Transitions (Handover Processes)mentioning
confidence: 99%
“…These included advanced nursing roles, physiotherapy, general practitioners, scribes and physician assistants, pharmacy, and mental health services, as well as the development of professional skills. [28]. For example, Identification, Situation, Background, Assessment, Requirements and Requests (ISBAR) is a tool for face-to-face beside handover [27][28][29][30].…”
Section: Team Composition Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges in interprofessional cooperation can compromise the care for patients [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The challenges are rooted in different aspects, including communication problems [ 9 , 10 , 11 , 12 ], or hierarchical power structures [ 13 , 14 , 15 ]. While growing into the field, roles, norms, values and beliefs are formed [ 16 , 17 , 18 ] and thus different aspects of care might be prioritized differently depending on professions and specialties [ 19 , 20 , 21 , 22 , 23 , 24 , 24 ].…”
Section: Introductionmentioning
confidence: 99%